2012
DOI: 10.1210/er.2011-1060
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin and Dickkopf-1 as Therapeutic Targets in Bone Diseases

Abstract: The processes of bone growth, modeling, and remodeling determine the structure, mass, and biomechanical properties of the skeleton. Dysregulated bone resorption or bone formation may lead to metabolic bone diseases. The Wnt pathway plays an important role in bone formation and regeneration, and expression of two Wnt pathway inhibitors, sclerostin and Dickkopf-1 (DKK1), appears to be associated with changes in bone mass. Inactivation of sclerostin leads to substantially increased bone mass in humans and in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
299
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(306 citation statements)
references
References 225 publications
(237 reference statements)
4
299
1
2
Order By: Relevance
“…These findings strongly suggest that osteocytes also might mediate anabolism induced by systemic activation of the pathway, with inhibitors of GSK3β or neutralizing antibodies of sclerostin, or even in human mutations of components of the Wnt pathway (4). The fact that osteocytes comprise most of the cells in bone might explain why bone anabolism is the most patent outcome of systemic Wnt activation, even when inhibition of resorption might be also manifested in some instances (36).…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that osteocytes also might mediate anabolism induced by systemic activation of the pathway, with inhibitors of GSK3β or neutralizing antibodies of sclerostin, or even in human mutations of components of the Wnt pathway (4). The fact that osteocytes comprise most of the cells in bone might explain why bone anabolism is the most patent outcome of systemic Wnt activation, even when inhibition of resorption might be also manifested in some instances (36).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are required to investigate the roles of Wnt/β-catenin, as well as numerous other signaling pathways, in the occlusal hypofunction status and their underlying mechanisms. Sclerostin is emerging as a promising therapeutic target in bone disease therapy (43). Various animal studies demonstrated that the sclerostin antibody was effective in preventing unloading-induced osteoporosis (44,45).…”
Section: B a C Dmentioning
confidence: 99%
“…The anti-SOST antibody (Scl-Ab) has shown very promising results in both human and animal models of low bone mass disorders and fracture healing. To avoid redundancy and to give full attention to the exciting results from Scl-Ab studies, we encourage you to read the recently published and highly thorough review by Ke et al (253).…”
Section: Sclerostinmentioning
confidence: 99%